Exploring the impact of athletic identity on gender role conflict and athlete injury fear avoidance in male English professional academy football players - Cranswick, I.; Tod, D.; Clarke, P.; Jones, A. (Science and Medicine in Football, 2024)
Men`s academy football can encourage a commitment to the athletic role and masculine norms. When injured, the ability to fulfil an athletic masculine identity is threatened and athletes may experience injury fear-avoidance behaviours as part of a negative injury appraisal. The aim of the study was to explore whether higher athletic identity (AI) was associated with higher gender role conflict and injury-related fear-avoidance. Seventy-two male English academy footballers completed an Athletic Identity Measurement Scale (AIMS), Gender Role Conflict Scale (GRCS), and Athlete Fear Avoidance Questionnaire (AFAQ) based on self-reported historical injuries. Correlational analyses were conducted for all variables, and a one-way ANOVA was used to compare high, moderate, and low AI. AIMS was significantly positively correlated with two GRCS subscales: success, power, and competition (SPC) and restricted affectionate behaviour between men (RAM). AIMS exclusivity also positively correlated with SPC and AIMS negative affectivity positively correlated with GRCS total and RAM. Additionally, the current study showed that high and moderate levels of AI had significantly higher levels of total GRCS than those with low AI. No significant results were found for AIMS, GRCS, and AFAQ. Results suggest that players with higher and more exclusive AI may be susceptible to masculine role conflicts, specifically, SPC and RAM, especially when there is a risk to their athletic role. The current study informs sport and health professionals of the need to monitor AI and masculine conformity in academy-level footballers to minimise gender-role conflict and potential maladaptive rehabilitation responses when their identities are threatened.